Hippocampal Signatures of Episodic Memory: Evidence from Single-Unit Recording Studies - Griffin, Amy L.; Hallock, Henry L. (Frontiers in Behavioral Neuroscience, 2013)
What hippocampal neural firing patterns signal memory and, more importantly, how is this memory code used by associated structures to translate a memory into a decision or action? Candidate hippocampal activity patterns will be discussed including (1) trajectory-specific firing of place cells with place fields on an overlapping segment of two (or more) distinct trajectories (2) prospective firing of hippocampal neurons that signal an upcoming event or action, and (3) place cell remapping to changes in environment and task. To date, there has not compelling evidence for any of these activity patterns being the neural substrate of episodic memory. New findings suggest that learning and memory processes are emergent properties of interregional interactions and not localized within any one discrete brain region. Therefore, the next step in understanding how remapping and trajectory coding participate in memory coding may be to investigate how these activity patterns relate to activity in anatomically-connected structures such as the prefrontal cortex.